2018
DOI: 10.1080/02656736.2018.1475684
|View full text |Cite
|
Sign up to set email alerts
|

Local tumor progression after ultrasound-guided percutaneous microwave ablation of stage T1a renal cell carcinoma: risk factors analysis of 171 tumors

Abstract: US-guided percutaneous MWA for T1a RCC achieved a relatively low LTP incidence rate. Tumors adjacent to the renal pelvis or bowel increased the potential of LTP occurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…After repeated MWA(s), a secondary efficacy of 99% was reached for T1a tumours. In the literature, primary efficacy rates of MWA from 84.6 to 100% are reported [8,11,14,22,29]. Therefore, the primary and secondary efficacy of T1a tumours underpins the existing evidence supporting MWA for the treatment of T1a RCC lesions.…”
Section: Discussionmentioning
confidence: 99%
“…After repeated MWA(s), a secondary efficacy of 99% was reached for T1a tumours. In the literature, primary efficacy rates of MWA from 84.6 to 100% are reported [8,11,14,22,29]. Therefore, the primary and secondary efficacy of T1a tumours underpins the existing evidence supporting MWA for the treatment of T1a RCC lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Use of both US and CT during the ablative procedure, might also increase the ability to immediately detect a vital unablated residual tissue, and thus to guide an immediate intraprocedural second ablation. The possible occurrence of an incomplete ablation is among the drawbacks of image-guided thermal ablations, and can particularly occur in case of large or centrally located tumors [30][31][32][33]. However, one of the principal aims of application of image-guided thermal ablation is to lower the invasiveness of treatment in frail patients unsuitable for surgery, or to minimize renal function damage particularly when surgery would require total nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, the need of multiple treatments is generally accepted and taken into account during multidisciplinary discussions when establishing the patient treatment strategy. In fact, with a second ablation complete tumor ablation can be achieved in the large majority of cases [30,31,34]. Furthermore, patients can have a local tumor progression during follow-up, develop new foci of renal tumors in the same or in the contralateral kidney, or distant metastases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is an extended literature regarding mid-and long-term outcomes of RFA and CA for RCCs, MWA has been less studied and there is still a lack of data concerning long term efficacy. The present study adds to the growing number of case series showing that CT-guided percutaneous microwave ablation (Figure 3) is an efficacious and safe technique in terms of achieving local tumor control and recurrence-free response on both a per lesion and per patient basis [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. The results of the current study showed efficient progression free (100%, 86.7%, 86.7% and 83.5% for 1, 6, 12 and 36 months, respectively), recurrence free (94.7%) and overall survival rates (mean 35.6 months), in a follow up time of 36 months.…”
Section: Discussionmentioning
confidence: 99%